1988
DOI: 10.1104/pp.86.4.1210
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Nodule Initiation in Cowpea and Soybean

Abstract: When serial dilutions of a suspension of Bradyrhizobium japonicum strain 138 were inoculated onto both soybean and cowpea roots, the formation of nodules in the initially susceptible region of the roots of both hosts was found to be linearly dependent on the log of the inoculum dosage until an optimum dosage was reached. Approximately 30-to 100-fold higher dosages were required to elicit half-maximal nodulation on cowpea than on soybean in the initially susceptible zone of the root. However, at optimal dosages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 13 publications
2
13
0
Order By: Relevance
“…The relative location of nodules on the root system is a useful index of the time taken for infection, i.e. nodules located on the upper part of the root system are those that were initiated earlier than those on the lower parts of the root system (Bhuvaneswari et al 1988;. Thus, the increased crown nodulation observed on co-inoculated M. truncatula in this study further supports the data demonstrating that root infection occurred earlier with co-inoculation.…”
Section: Discussionsupporting
confidence: 79%
“…The relative location of nodules on the root system is a useful index of the time taken for infection, i.e. nodules located on the upper part of the root system are those that were initiated earlier than those on the lower parts of the root system (Bhuvaneswari et al 1988;. Thus, the increased crown nodulation observed on co-inoculated M. truncatula in this study further supports the data demonstrating that root infection occurred earlier with co-inoculation.…”
Section: Discussionsupporting
confidence: 79%
“…The highest nodule number came from Sudan 1 (21.7 nodules/plant), followed by IT8282E-16 (18.9), IT95-1090-12 (14.42) and 1T99K-1060 (14.0) Only two entries (Sudan 1 and IT99K-1060) appear to give grain and forage yields of about 2 tha -1 or more and high nodule numbers. These results concur with the ranges of 3-21 nodules per plant reported by Bhuvaneswari et al (1998). Ndor et al (2012) showed that nodules per plant in cowpeas increased from 20 to 32 when P application was raised from 0 to 40 kg ha -1 P. The authors reported cowpeas yield increase from about 1.0 to 1.5 t ha -1 with associated with the same P application rates.…”
Section: Nodulationsupporting
confidence: 87%
“…Highly promiscuous plant hosts are able to nodulate with a wide range of rhizobia strains and at low bacterial densities, while less promiscuous hosts show greater strain specificity and require higher bacterial densities before they nodulate (Roughley 1987;Bhuvaneswari, Lesniak & Bauer 1988;Thrall, Burdon & Woods 2000;Thrall et al 2005Thrall et al , 2007. In addition, plant hosts themselves influence the availability of rhizobia in the soil (Thrall, Burdon & Woods 2000), with rhizobia population numbers increasing rapidly in response to compatible plant hosts (Purchase & Nutman 1957;Parker 2001) and declining when they are absent (Thrall et al 2001).…”
Section: Introductionmentioning
confidence: 99%